Field studies on the effect of cold on man, with special reference to metabolic rate - Wilson, Ove (C.W.K. Gleerup, 1966)
Resyme av dr.avh. - 7 enkeltskr. ib. med resymeet
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; fysiologi; kuldeeksponering; kuldetoleranse; medisin

Man in Antarctica - Rodahl, Kaare (Science in Antarctica. Part 1: The Life sciences in Antarctica, 1961)
Keywords: Antarktis; ekspedisjoner; forskning; fysiologi; kuldetoleranse; medisin; polarområdene

Changes in body-weight of men in the Antarctic - Wilson, Ove (British Journal of Nutrition, 1960)
Keywords: Dronning Maud Land; Maudheimekspedisjonen; NBSAE 1949-52; NSBX 1949-52; Norsk-britisk-svenske antarktisekspedisjon; fysiologi; observasjoner